Using ADDIE Model to develop STORE (Students on Recreation): An Environmental Exploration-Based Learning Strategy in Merdeka Curriculum - Tristiana, Yeni; ., Senowarsito; Nur'aini, Siti (KnE Social Sciences, 2024)
English is an international language that all students must learn so they can speak, communicate, and interact with the international community both actively and passively. Unfortunately, many teachers have difficulties in creating a communicative, comfortable, and enjoyable learning and teaching atmosphere. This results in students being less enthusiastic about learning English and feeling bored. This research aims to develop STORE (students on recreation) learning strategy based on the environmental exploration of English language learning in the implementation of the Merdeka Curriculum and to enhance students’ well-being using the STORE learning strategy. The research method used wasresearch and development with the ADDIE model (analysis, design, development, implementation, and evaluations). To collect data, the researcher used questionnaires, interviews, and observation instruments. Data were obtained from 64 7th-grade students and three English teachers at SMP Negeri 1 Bangsri. For data processing, researchers used descriptive statistics to analyze learning needs for fun outdoor recreation. Research activities were carried out through the following stages. Initial stage: needs analysis; Stage II: creating a STORE learning plan; Stage III: limited trials and evaluation. Stage IV: Draft revision; Stage V: Design validation; Stage VI: implementation and evaluation; Final stage: dissemination of research results. The research showed that the students’ learning motivation had increased. The participants indicated their preference for outdoor learning because they could explore their environment and learn simultaneously. In conclusion, the environmental exploration learning strategy can be applied to enhance students’ interest in learning English and also to implement the Merdeka curriculum Keywords: ADDIE model, environmental exploration, independent curriculum, STORE learning